Operator Method to Solve Fractional Order Linear Differential Equations via Proportional α Derivative - Ajay Dixit; Amit Ujlayan (International Journal of Mathematics And its Applications, 2019)
In this study, we proposed an operator method for fractional order linear differential equations with constant coefficients. The form of fractional derivative, used in this article is proportional α derivative, introduced recently. Furthermore, to demonstrate the efficiency of the proposed operator method for fractional differential equations some numerical examples have discussed. One may verify the result for α=1.